Quasi-experimental designs for community-level public health violence reduction interventions: a case study in the challenges of selecting the counterfactual - Roman, Caterina Gouvis (Journal of experimental criminology, 2018)
We highlight the importance of documenting the step-by-step processes used for the selection of comparison areas when evaluating a community-level intervention that targets a large-scale community.